Implikasi Re-Eksistensi Tap Mpr dalam Hierarki peraturan perundang- Undangan terhadap Jaminan atas Kepastian Hukum yang adil di Indonesia - Wicaksono, Dian Agung (Mahkamah Konstitusi Republik Indonesia, 2013)
Post-enactment of Act Nr. 12 of 2011, MPR Decree was put again the hierarchy of legislation, which cause problems in the context of the state of law of Indonesia. This was normative legal research. Now, the number of MPR Decree is only 6 decrees remaining, so re-existence and placement of MPR Decree is not relevant. Hierarchy should be made by simplification approach by reducing the nomenclature of law in the hierarchy of legislation. MPR Decree should have not been included in the hierarchy, especially under the Constitution. If the MPR Decree still be placed under the Constitution, we need to hold the mechanism to review MPR Decree, if there is a contradiction with the Constitution or the restriction of human rights, which actually should not be limited by the MPR.